Sorghum hybrid seed production and quality maintenance - Kannababu, N; Sooganna; Raghunath, K; Bhat, B Venkatesh (Indian Farming, 2023)
Production of best quality seeds to meet the needs of the grower should be the main endeavour of sorghum improvement projects and seed agencies. Many limitations prevent or alter reproductive strategy of sorghum parental lines during hybrid seed production. Therefore, care must be taken for seed production that offer optimum climatic package during crop growth period. Seed certificationagencies have an important role to play in certified hybrid seed production and distribution, because the crop performance is dependent on the quality of the certified seed used. Flowering behavior of the hybrid parents, productivity vs cost, and climatic conditions, particularly during the stages of flowering and seed filling should be important considerations to select an area for hybrid seed production. Good seed set in seed parent is possible by synchronization of flowering of pollen donor and pollen receptor, and adopting effective seed crop management practices. Regular guidance to seed growers by technical staff during the entire season of hybrid seed production facilitates the production of quality seeds of sorghum hybrid.